Mitochondrial rewiring with small-molecule drug-free nanoassemblies unleashes anticancer immunity - Ren, Lulu; Wan, Jianqin; Li, Xiaoyan; Yao, Jie; Ma, Yan; Meng, Fanchao; Zheng, Shusen; Han, Weidong; Wang, Hangxiang (Nature communications, 2024)
The immunosuppressive tumor microenvironment (TME) remains a major obstacle to tumor control and causes suboptimal responses to immune checkpoint blockade (ICB) therapy. Thus, developing feasible therapeutic strategies that trigger inflammatory responses in the TME could improve the ICB efficacy. Mitochondria play an essential role in inflammation regulation and tumor immunogenicity induction. Herein, we report the discovery and characterization of a class of small molecules that can recapitulate aqueous self-assembly behavior, specifically target cellular organelles (e.g., mitochondria), and invigorate tumor cell immunogenicity. Mechanistically, this nanoassembly platform dynamically rewires mitochondria, induces endoplasmic reticulum stress, and causes apoptosis/paraptosis-associated immunogenic cell death. After treatment, stressed and dying tumor cells can act as prophylactic or therapeutic cancer vaccines. In preclinical mouse models of cancers with intrinsic or acquired resistance to PD-1 blockade, the local administration of nanoassemblies inflames the immunologically silent TME and synergizes with ICB therapy, generating potent antitumor immunity. This chemically programmed small-molecule immune enhancer acts distinctly from regular cytotoxic therapeutics and offers a promising strategy for synchronous and dynamic tailoring of innate immunity to achieve traceless cancer therapy and overcome immunosuppression in cancers. Mitochondria disruption can elicit immune responses. Here the authors report the design and characterization of mitochondria targeting drug-free nanoassemblies promoting immunogenic cell death and anti-tumor immune responses in preclinical models.